Phase-change metamaterial for tunable polarization conversions in terahertz region - Surawut Wicharn; Prathan Buranasiri (My University, 2024)
In this study, a phase-change metamaterial (PCM) is proposed to be applied as tunable terahertz (THz) polarization converter. The structure of PCM consists of 4 layers such as hyperbolic medium (HM) layer, vanadium dioxide (VO2) layer, the polyimide (PI) layer, and gold (Au) gratings, respectively. The HM layer is made by two-dimensional arrangement of gold (Au) nanowires in x-y plane immerged in PI host slab. The polarization converting characteristics of PCM structure is investigated numerically by using anisotropic transfer-matrix method (ATMM). The numerical results show that, when the VO2 is in insulating state, the PCM structure provides transmitted cross-linear polarization conversion and when the VO2 is changed to conducting state, the PCM structure gives both reflective cross-linear polarization and linear-to-circular polarization conversions.
Keywords: Metamaterials and Metasurfaces Applications; Millimeter-Wave Propagation and Modeling; Advanced Antenna and Metasurface Technologies